Clinical companion for Fundamentals of nursing : just the facts - Peterson, Veronica; Potter, Patricia Ann (Elsevier Mosby, 2013)
Provides information on fundamentals of nursing you'll need to know in your clinicals. From definitions and abbreviations to dosage calculations and lab values, this title presents the guidelines and clinical information.